Cross country maize market linkages in Africa: integration and price transmission across local and global markets. (31st October 2018) - Pierre, Guillaume; Kaminski, Jonathan
Abstract: In order to study short‐run price shock propagation, we model twenty seven Sub‐Saharan Africa (SSA) domestic maize markets within a Global Vector Autoregression framework. The main purpose is to fully embed multilateral trade flows as a way to better structure local price transmission dynamics and interdependencies, and get a more comprehensive picture of food price shocks propagation. We found significant between‐country market contagion and prompt regional price shock propagation when trade connection exists. Yet, the integration of SSA domestic maize markets within the continent and with global markets remains generally weak. Furthermore, under regular market conditions, most local price series appear to be more responsive to regional neighbors than to global shocks.